2018
DOI: 10.1016/j.nanoen.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Multi-electric field modulation for photocatalytic oxygen evolution: Enhanced charge separation by coupling oxygen vacancies with faceted heterostructures

Abstract: A fundamental challenge of photocatalysis is developing efficient strategies to suppress the recombination of photogenerated charge carriers. Herein, ZnO/BiVO4 hierarchical nanostructures were exemplified to demonstrate new concept of multi-electric field-assisted charge separation. The contribution of both facet engineering and defect modulation to the facilitated photocatalysis was confirmed by both experimental observations and theoretical calculations. Such integration of built-in fields in faceted BiVO4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 47 publications
4
43
0
Order By: Relevance
“…For example, {001} and {101} facets of TiO 2 , two most common facets of anatase phase, usually exhibit different adsorption characteristics and redox abilities during the photocatalytic reaction [24,25,26,27]. Our research further revealed the significant contribution of facet-dependent formation of oxygen vacancy defects on the interfacial behavior of photo-induced charge carriers [28]. In this regard, it is a critical point to investigate the impact of crystal facets and defects on the charge separation in MoS 2 -grafted faceted TiO 2 .…”
Section: Introductionmentioning
confidence: 79%
“…For example, {001} and {101} facets of TiO 2 , two most common facets of anatase phase, usually exhibit different adsorption characteristics and redox abilities during the photocatalytic reaction [24,25,26,27]. Our research further revealed the significant contribution of facet-dependent formation of oxygen vacancy defects on the interfacial behavior of photo-induced charge carriers [28]. In this regard, it is a critical point to investigate the impact of crystal facets and defects on the charge separation in MoS 2 -grafted faceted TiO 2 .…”
Section: Introductionmentioning
confidence: 79%
“…Partial holes on {110} facets were recombined with the electrons that enriched on the endpoints of ZnO nanorods to form a Z‐scheme heterojunction, which led to efficient charge separation. [ 160 ] Besides, the mixed‐phase BiVO 4 (monoclinic and tetragonal phases) were applied as the bridge to construct BiVO 4 /g‐C 3 N 4 Z‐scheme junction for accelerating the charge separation and water oxidation (Figure 25g). [ 161 ] To realize the tight coupling between α ‐Fe 2 O 3 and g‐C 3 N 4 , an SSR route was carried out to synthesize the 2D/2D α ‐Fe 2 O 3 /C–g‐C 3 N 4 (C–g‐C 3 N 4 indicates g‐C 3 N 4 with amorphous carbon).…”
Section: Strategies For Enhancing Photocatalytic Oxygen Evolutionmentioning
confidence: 99%
“…The effect of oxygen vacancies on the BiVO 4 PEC performance is still under debate in the literature. Recent works indicate that oxygen vacancies can have multiple roles on the PEC‐WS performance of metal oxides . From the positive side, it is commonly accepted that oxygen vacancies inside the bulk medium improve the free carrier concentration and consequently lead to better charge carrier transport .…”
Section: Resultsmentioning
confidence: 99%